Respuesta :
(1,0),(6,-3)
slope(m) = (-3 - 0) / (6 - 1) = -3/5
y - y1 = m(x - x1)
slope(m) = -3/5
(6,-3)....x1 = 6 and y1 = -3
now sub....and pay attention to ur signs
y - (-3) = -3/5(x - 6)......this is not the final answer....but it seems to be what ur question is asking for.
slope(m) = (-3 - 0) / (6 - 1) = -3/5
y - y1 = m(x - x1)
slope(m) = -3/5
(6,-3)....x1 = 6 and y1 = -3
now sub....and pay attention to ur signs
y - (-3) = -3/5(x - 6)......this is not the final answer....but it seems to be what ur question is asking for.
Answer:
[tex]y-(-3)=-\frac{3}{5}(x-6)[/tex]
Step-by-step explanation:
If a line passes through two points [tex](x_1,y_1)[/tex] and [tex](x_2,y_2)[/tex], then equation of line is
[tex]y-y_1=\frac{y_2-y_1}{x_2-x_1}(x-x_1)[/tex]
The point slope form of line is
[tex]y-y_1=m(x-x_1)[/tex]
where, m is slope.
It is given that the line passes through the points (1,0) and (6,-3).
In the given equation y-(-3)=___, [tex]y_1=-3[/tex]. It means
[tex](x_1,y_1)=(6,-3)[/tex]
[tex](x_2,y_2)=(1,0)[/tex]
So, the point slope form of the given line is
[tex]y-(-3)=\frac{0-(-3)}{1-6}(x-6)[/tex]
On simplification we get
[tex]y-(-3)=-\frac{3}{5}(x-6)[/tex]
Therefore the point slope form of the given line is [tex]y-(-3)=-\frac{3}{5}(x-6)[/tex].